REFLECTIVE TEACHING IN THE ENGLISH CLASSROOMS: TEACHERS' BELIEFS AND PRACTICES - Diana Oktavia, - (2019)
Highly competent teachers are desirable to help improve the quality of education in Indonesia. In reality, reflective teaching is still challenging to be carried out by teachers. Yet, continuously doing reflective teaching can be considered as a way to help enhance teachers' competencies, as also required by the government. For this reason, it is important to delve into teachers' understandings of reflective teaching, both in terms of their beliefs and practices. The present study thus aims to: (1) explore the beliefs about reflective teaching held by one novice teacher and one experienced teacher teaching in the same school, and (2) explore the ways these beliefs are reflected in the teachers' teaching practices. Adopting a qualitative multiple-case studies design, the data of the study were collected through semi-structured in-depth interviews, informal interviews, classroom observations, document analysis, and field notes. In analyzing the data, theories of beliefs proposed by Pajares (1992), and Richardson (1996), as well as theories of reflective practice proposed by Schon (1983), and Griffiths and Tann (1992) were used as the main theoretical frameworks. The major findings of the study reveal that the two teachers have some beliefs in common, i.e., perceiving reflective teaching as an important aspect to develop teachers' knowledge. The teachers' beliefs are also reflected in their teaching practices most of the time, primarily through reflection-in-action. Ultimately, this study is expected to promote the importance of doing reflective teaching among teachers as a way to improve teaching practices and develop their professionalism; Guru-guru yang sangat kompeten diharapkan untuk membantu meningkatkan kualitas pendidikan di Indonesia. Pada kenyataannya, pengajaran reflektif masih menjadi tantangan untuk dilakukan oleh guru-guru. Padahal, melakukan pengajaran reflektif secara berkelanjutan dapat dipertimbangkan sebagai cara untuk membantu meningkatkan kompetensi guru-guru, sebagaimana dipersyaratkan pula oleh pemerintah. Oleh karena itu, penting untuk menggali pemahaman guru-guru mengenai pengajaran reflektif, baik dalam keyakinan mereka maupun dalam prakteknya. Jadi, penelitian ini bertujuan untuk: (1) mencari tahu keyakinan yang dipegang oleh seorang guru pemula dan seorang guru berpengalaman yang mengajar di sekolah yang sama terhadap pengajaran reflektif, dan (2) mencari tahu cara guru-guru tersebut dalam menerapkan keyakinan mereka dalam praktek mengajar mereka. Dengan mengaplikasikan desain studi kualitatif kasus ganda, data dalam penenlitian ini diambil dari wawancara semi-struktural yang mendalam, wawancara tidak resmi, observasi kelas, analisa dokumen, dan catatan lapangan. Dalam menganalisa data, teori-teori mengenai keyakinan yang diprakarsai oleh Pajares (1992), dan Richardson (1996), juga teori-teori mengenai pengajaran reflektif yang diprakarsai oleh Schon (1983), dan Griffiths dan Tann (1992) digunakan sebagai acuan teori-teori utama. Penemuan utama dalam penelitian ini mengungkapkan bahwa kedua guru tersebut memegang banyak keyakinan yang sama, seperti halnya mempercayai bahwa pengajaran reflektif sebagai aspek yang penting untuk mengembangkan pengetahuan guru-guru. Keyakinan-keyakinan mereka juga sering tergambar dalam praktek mengajar mereka, terutama melalui refleksi-dalam-kelas. Pada akhirnya, penelitian ini diharapkan untuk mempromosikan pentingnya melakukan pengajaran reflektif diantara guru-guru sebagai salah satu cara untuk meningkatkan praktek mengajar dan mengembangkan keprofesionalan mereka